Strategi Pengelolaan Keuangan di MTs Muhammadiyah 5 Daun Kecamatan Sangkapura Kabupaten Gresik - Fourfiyanti, Ayu Wahyuning (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Financial management strategy is very important for every educational institution. school financial management can determine whether or not educational institutions are efficient in carrying out the learning process. If financial management can be done well, the learning process will run effectively and efficiently. school financial management must include financial planning, procurement of school financial resources, and school financial accountability. The research approach used in this study researchers used a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Then the technique of checking the validity of the data is depth of observation, triangulation, and membercheck. The results in this study indicate that 1). The financial management strategy at MTs Muhammadiyah 5 Daun is carried out by making financial planning in advance based on a priority and non-priority scale. Financial planning at Muhammadiyah 5 Daun MTs includes the development of content standars, process standards development, development of graduate competence standards, developing standards of educators and educational personnel, developed standards of facilities, development management standards, development financing standards and development of educational evaluation standards. 2). The procurement of sources of funds at MTs Muhammadiyab 5 leaves comes from BOS funds, parents of students, the community, alumni, school entrepreneurs, and Lazismu. 3). Financial accountability at MTs Muhammadiyah 5 Daun is carried out with a general cash book, cash assistant cash book, bank assistant cash book, and tax assistant cash book.